Pengadilan Tata Usaha Negara Dalam Memberikan Perlindungan Hukum Kepada Masyarakat - Zamzami, Abid; Muslim, Shohib (Widya Yuridika, 2023)
Indonesia is a rule of law country, which means that all government administration actions must be based on law. One of the elements of a rule of law according to Friedrich Julius Stahl is the existence of Administrative Justice (PTUN) as a means of control over government actions as well as a medium for society to seek justice if the government's actions suffer losses. The existence of the State Administrative Court is a form of legal protection for the public for all legal actions carried out by the government so that it is in line with the provisions stipulated in statutory regulations and prevents the public from being exposed to arbitrary actions carried out by the Government. The enactment of Law Number 30 of 2014 concerning Government Administration has expanded the authority of the State Administrative Court in examining administrative decisions. With this extension, it is not my decision that can be used as an object of dispute, but positive fictitious decisions can also be used as an object of dispute.